INTEGRATING INTERACTIVE LEARNING MEDIA TO IMPROVE STUDENTS COMPREHENSION OF ISLAMIC RELIGIOUS EDUCATION: A STUDY AT MIFTAHUL ULUM BILINGUAL JUNIOR HIGH SCHOOL - Tia Lasmi Saputri; Muhammad Irfan; Akhmad Riadi (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2025)
Abstract: This study addresses students limited comprehension of Islamic Religious Education (PAI) content, a problem attributed to the dominance of lecture-based instruction and the minimal use of digital learning media. Employing Classroom Action Research (CAR) based on the Kemmis and McTaggart spiral model, the intervention was implemented across two cycles consisting of planning, action, observation, and reflection. Interactive digital resources , as YouTube instructional videos, animated PowerPoint materials, and Chromebooks, were incorporated to enhance engagement and facilitate understanding of complex concepts. Data were collected through observations, interviews, documentation, and cognitive assessments. The findings show a significant improvement in learning outcomes: the average pre-cycle score of 78 increased to 85 in Cycle I and further to 92 in Cycle II, supported by the use of digital quizzes and Chromebook-based group discussions that strengthened students motivation and comprehension. These results demonstrate that integrating interactive digital media can effectively enhance students engagement, understanding, and retention of Islamic Religious Education content. Keywords: Islamic Religious Education, Interactive Media, Classroom Action Research, Chromebook, Learning Outcomes.